Subjective and objective assessment of sedentary behavior among college employees - Samuel Headley; Jasmin Hutchinson; Sarah Wooley; Kristen Dempsey; Kelvin Phan; Gregory Spicer; Xanne Janssen; Jerold Laguilles; Tracey Matthews (BMC, 2018)
Abstract Background High levels of sedentary behavior are linked to increased mortality. In the United States, individuals spend 55-70% of their waking day being sedentary. Since most individuals spend large portions of their daily lives at work, quantifying the time engaged in sedentary behavior at work is emerging as an important health determinant. Studies profiling academic institutions, where a variety of personnel with diverse job descriptions are employed, are limited. Available studies focus mostly on subjective methods, with few using objective approaches. Therefore, the purpose of the current study was to assess sedentary behavior among all occupational groups of a college in the Northeastern United States utilizing both a subjective and an objective method. Methods College employees (n = 367) completed the Occupational Sitting and Physical Activity Questionnaire (OSPAQ). A sub-sample of these employees (n = 127) subsequently wore an activPAL3 accelerometer 24 h per day for seven consecutive days. Outcome variables were time spent sitting, standing, stepping, and total number of steps. To assess fragmentation of sedentary behavior, the average duration of a sitting bout and sitting bouts/sitting hour were calculated. Differences between administrators, faculty, and staff, were analyzed using multivariate and univariate analyses of variance. Results The OSPAQ results indicated that administrators spent more of their working day sedentary (73.2 ± 17.7%) than faculty members (58.5 ± 19.6%, p < 0.05). For the objective phase of the study, complete data were analyzed from 86 participants. During a waking day, administrators (64.0 ± 8.1%) were more sedentary than faculty (56.0 ± 7.9%, p < 0.05) and fragmented their sitting less than staff (3.7 ± 0.7 and 4.5 ± 7.9 bouts of sitting/sitting hour, respectively; p < 0.05). This pattern was also seen during working hours, with administrators (4.9 ± 2.1) taking fewer breaks per hour than staff (6.9 ± 3.0, p < 0.05). Conclusions Administrators are the most sedentary members of the campus community. However, overall, the level of sedentary behavior among employees was high. This study highlights the need for sedentary behavior interventions in the college/university environment.